Implementasi Kurikulum Merdeka Jalur Mandiri di SD Negeri Gugus 1 Kecamatan Gunung Talang Kabupaten Solok - Primadona, Sus; Adripen, Adripen; Demina, Demina (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research is motivated by the implementation of the independent curriculum for independent pathways changing at the elementary school level after the COVID-19 pandemic. This research is qualitative. The research location is in the public elementary school in Gugus 1, Gunung Talang Subdistrict. The data collection techniques used were semi-structured interviews, observation sheets, and documentation. Data analysis techniques are condensing data, displaying data, drawing conclusions, and verifying data. The results showed that 1) There is a change in the form of planning in the implementation of the independent pathway curriculum which focuses on aspects of curriculum, human resources, financing, facilities and infrastructure. 2) Implementation of the independent pathway curriculum begins with the formulation of learning objectives, preparation of a flow of learning objectives, diagnostic assessment at the beginning of learning, technical guidance and socialization of teachers and parents, and fulfilment of learning resources and learning media. 3) The form of supervision of the implementation of the independent curriculum is carried out on aspects of the learning process, preparation of learning tools, and reports on learning outcomes.